2018
DOI: 10.1021/acs.cgd.8b00348
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Crystal Landscape of 3-Methyl-2-phenylbutyramide: Crystallization of Metastable Racemic Forms from the Stable Conglomerate

Abstract: In the solid state, (±)-3-methyl-2-phenylbutyramide 1 spontaneously resolves into a conglomerate (Form I) that crystallizes in a racemic form (Form II) upon melting followed by vapor crystallization, a rarely reported phenomenon. An additional racemic polymorph, Form III, has been characterized, and the thermodynamic relationship between the three forms established by a variety of computational and experimental methods including grinding, slurry crystallization, and seeding techniques. Both racemic Forms II an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 57 publications
1
6
0
Order By: Relevance
“…Crystallization-based techniques are essential strategies to obtain chiral compounds, including preferential crystallization, preferential enrichment, classical chemical resolution, , and cocrystallization-based resolution. , Among them, preferential crystallization has the advantages of simplicity, economy, and high throughput, and the target products can be mass-produced by regulating the crystallization kinetics by seeding the desired enantiomer. However, it is only applicable to conglomerates that only account for 5–10% of racemates . Therefore, chiral selectors have been used to reconstitute a pair of conglomerate-like diastereomers or enantiospecific salts/cocrystals with the remaining racemic compounds (90–95%).…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…Crystallization-based techniques are essential strategies to obtain chiral compounds, including preferential crystallization, preferential enrichment, classical chemical resolution, , and cocrystallization-based resolution. , Among them, preferential crystallization has the advantages of simplicity, economy, and high throughput, and the target products can be mass-produced by regulating the crystallization kinetics by seeding the desired enantiomer. However, it is only applicable to conglomerates that only account for 5–10% of racemates . Therefore, chiral selectors have been used to reconstitute a pair of conglomerate-like diastereomers or enantiospecific salts/cocrystals with the remaining racemic compounds (90–95%).…”
Section: Introductionsupporting
confidence: 70%
“…However, it is only applicable to conglomerates that only account for 5−10% of racemates. 10 Therefore, chiral selectors have been used to reconstitute a pair of conglomerate-like diastereomers or enantiospecific salts/cocrystals with the remaining racemic compounds (90−95%). For instance, Lmalic acid can form diastereomeric pairs with (RS)praziquantel and (RS)-3,5-bis(trifluoromethyl)-α-methyl-N-methylbenzylamine.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The relative stability of polymorphs was simulated using DFT. Lattice energy is an important parameter, which can reflect the stability of the crystals, as well as explain and predict the characteristics of crystals. The calculation data of the lattice energy of different DFL forms are summarized in Table , in which the crystal form with zero relative energy was the most stable. The order of thermodynamic stability of the five crystal forms of DFL was as follows: I > III > IV > VI > V. From the Hirshfeld analysis, Form I has the highest contributions of main hydrogen bond interaction (O ··· H bond).…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that the crystals of this compound are built of ribbon synthons that can be described by a R 2 2 (8) R 4 2 (8) graph set. 10 For 2-(4-t-butylphenyl)propionamide, only the racemic form has been studied (ZEPGAF), and a R 2 2 (8) R 6 4 (16) layer synthon was observed. 12 In one of our previous studies, 8 we solved crystal structures of racemic and enantiopure forms of 2-phenylbutyramide (VOQGUF, VOQHAM, and VOQHEQ) and unambiguously assigned the absolute configurations of its enantiomers.…”
Section: ■ Introductionmentioning
confidence: 99%